(6xy-3)(3xy+5)=

Simple and best practice solution for (6xy-3)(3xy+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6xy-3)(3xy+5)= equation:


Simplifying
(6xy + -3)(3xy + 5) = 0

Reorder the terms:
(-3 + 6xy)(3xy + 5) = 0

Reorder the terms:
(-3 + 6xy)(5 + 3xy) = 0

Multiply (-3 + 6xy) * (5 + 3xy)
(-3(5 + 3xy) + 6xy * (5 + 3xy)) = 0
((5 * -3 + 3xy * -3) + 6xy * (5 + 3xy)) = 0
((-15 + -9xy) + 6xy * (5 + 3xy)) = 0
(-15 + -9xy + (5 * 6xy + 3xy * 6xy)) = 0
(-15 + -9xy + (30xy + 18x2y2)) = 0

Combine like terms: -9xy + 30xy = 21xy
(-15 + 21xy + 18x2y2) = 0

Solving
-15 + 21xy + 18x2y2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(-5 + 7xy + 6x2y2) = 0

Factor a trinomial.
3((-5 + -3xy)(1 + -2xy)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-5 + -3xy)' equal to zero and attempt to solve: Simplifying -5 + -3xy = 0 Solving -5 + -3xy = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3xy = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3xy = 0 + 5 -3xy = 0 + 5 Combine like terms: 0 + 5 = 5 -3xy = 5 Divide each side by '-3y'. x = -1.666666667y-1 Simplifying x = -1.666666667y-1

Subproblem 2

Set the factor '(1 + -2xy)' equal to zero and attempt to solve: Simplifying 1 + -2xy = 0 Solving 1 + -2xy = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2xy = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2xy = 0 + -1 -2xy = 0 + -1 Combine like terms: 0 + -1 = -1 -2xy = -1 Divide each side by '-2y'. x = 0.5y-1 Simplifying x = 0.5y-1

Solution

x = {-1.666666667y-1, 0.5y-1}

See similar equations:

| 0.9y-0.4y=6.5 | | d-10=-16 | | 4(t-5)+6t=5(2t+4)-11 | | x=(-5i)(-6i) | | -1/7-3/2w=4/5 | | -3(3s-5)-15=-3(8s+1)-3 | | x=(5+7i)-(6-8i) | | x=(5+7i)(6-8i) | | -2/3-1/4v=-1/5 | | 160.03=2.72w+14.84 | | 12(2)+15(2)-9+5=-3(2)+5-9 | | 5X+2X-3Y=13-2 | | 1-2(3x-4)=5x-2(3x-5) | | 1/2=-1/2x-6/5 | | -7/2+6/7x=-8/3 | | -2(3s-5)-10=-3(5s+3)-5 | | .24(18)+0.04x=0.08(24+x) | | 2r^2-6r/r-3 | | 5w^2+7w=6 | | 2p+7=5-(11p+6) | | 5/4+2y=4y-1/4 | | .3(6)+.05x=.15(30+x) | | lx-4l=3 | | 6x^2=12x-16/3 | | 6(v+1)-2v=2(2v+2)-11 | | 7+13y-5=9y+18-4y | | 11/6+1/5t=4 | | 3x+2x+2=9 | | 7822-3008= | | x^3-12x+35=0 | | 5k+24=k-8 | | 3x+14x+6=10 |

Equations solver categories